Modified Free Radial Forearm Fascia Flap Reconstruction of Lower Extremity and Foot Wounds: Optimal Contour and Minimal Donor-Site Morbidity - Medina, Miguel A., III; Salinas, Harry M.; Eberlin, Kyle R.; Driscoll, Daniel N.; Kwon, John Y.; Austen, William G., Jr.; Cetrulo, Curtis L., Jr. (Journal of Reconstructive Microsurgery, 2014)
Background Free tissue transfer is commonly required for reconstruction of distal third lower extremity injuries. Injuries involving the dorsal surface of the foot require thin pliable flaps. Musculocutaneous flaps are often too bulky to accommodate shoewear. Fasciocutaneous flaps, while an improvement, need secondary contouring procedures. The modified radial forearm fascial flap (MRFFF) may offer an alternative.Methods Twelve patients with distal third lower extremity wounds were reconstructed with MRFFF + split thickness skin graft. The modification in flap design leaves fascia radial to the pedicle unharvested, preserving sensibility of the dorsoradial aspect of the hand. Flaps were covered with a skin graft after inset. Donor sites were closed primarily.Results Nine wounds were traumatic—five with exposed hardware, one burn, one diabetic ulcer, and one wound dehiscence following sarcoma resection + radiation. Out of 12, 11 limbs were salvaged at 1 to 2 years follow-up. All patients ambulated on the reconstructed leg and wore a shoe comfortably. Average time to weight bearing was 2 months. The donor site was limited to 25-cm scar on the volar forearm. No persistent motor/sensory deficits occurred in donor arms.Conclusion MRFFF is an excellent flap for reconstruction of the distal lower extremity. Flap contour allows excellent shoe-fitting without secondary revisions. Replacement of the adipocutaneous flap on MRFFF donor site eliminates the need for a conspicuous donor-site skin graft. The ulnar orientation of the harvested fascia prevents sensory loss in the dorsal hand. The MRFFF provides the ideal replacement of “like with like” for selected distal lower extremity wounds.
Keywords: radial forearm fascia flap; lower extremity; foot; wound; microsurgical